Warped Product Submanifolds of Riemannian Product Manifolds - Falleh R. Al-Solamy; Meraj Ali Khan (Abstract and Applied Analysis)
We study warped product of the type Nθ×fNT and Nθ×fN⊥, where Nθ, NT, and N⊥ are proper slant, invariant, and anti-invariant submanifolds, respectively, and we prove some basic results and finally obtain some inequalities for squared norm of second fundamental form.